Stream Sentinels: Mayfly Diversity, Land Use, and Conservation in Algeria's Djurdjura Mountains - Labdaoui, Sarah; Samraoui, Farrah; Vuataz, Laurent; Gattolliat, Jean‐Luc; Sartori, Michel; Samraoui, Boudjéma (Aquatic conservation, 2024)
ABSTRACT Despite its biogeographical importance and high endemism, the freshwater biodiversity in Algeria and the wider arid region of North Africa has been significantly under‐researched and underestimated. Mayflies (Ephemeroptera) are crucial for the maintenance of ecological integrity of hydrosystems and could serve as indicators of changes of North African freshwater biodiversity. This study focuses on mayflies in Algeria, particularly in the Djurdjura Mountains, including the Djurdjura National Park in central‐northern Algeria. The aim is to establish an updated checklist, map the distribution of mayfly species and determine the ecological requirements of their assemblages. Twenty‐four mayfly taxa were identified during the study, including five new, undescribed species. Through multivariate analysis, the study revealed that land‐use practices, altitude and slope orientation significantly influenced mayfly assemblages in the studied streams. This study emphasises the urgent need for conservation action and lays the foundation for future research and conservation efforts that are essential to protecting the integrity of the critical freshwater habitats of the Djurdjura Mountains, which are hotspots for North African endemic species.